Economic and technological assessment of construction of primary health care centres in rural areas of the Russian Federation - G. A. Trunin; A. F. Baranova (Вестник университета, 2025)
The purpose of this work is to study technologies and economic factors for the construction of primary medical centres in rural areas of the Russian Federation (hereinafter referred to as RF) within the framework of the national project “Healthcare”. The subject of the study are economic factors and modular technologies for the construction of the primary health centres as well as the all-Russian dynamics of the development of obstetric stations using the example of the Vladimir region. The research methods include a systems approach, analysis of technical, public procurement documentation, and documentation of modular container manufacturers. Then photographic materials and video recording of the main construction stages of the obstetric points conducted by “Oblstroyzakazchik” have been studied. The authors have summarised the all-Russian trend and dynamics of the development of these points in the RF, have identified the key problems of organising their work and further operation, from which the requirements for modern obstetric points for the implementation of primary health care in rural areas follow. For the period from 2019–2021, 30 such objects are examined, the work progress is analysed, key problems of the construction delays in the region are identified, and violations during their construction are determined. For the rapid erection of medical facilities in rural areas, the choice of an architectural solution using modular block container technology is acceptable. The development of design and estimate documentation should be conducted with consideration to the technologies used as well as specific solutions of the factories producing ready-made modules. It should be recognised that assigning the task of purchasing and installing medical equipment to contractors is erroneous. The problems identified in the implementation of national projects have to be considered in terms of the execution of government contracts, management and engineering solutions.